Evaluation of the effects of single vision lenses with additional near-power on computer-induced asthenopia - Alionis,Aline Cristina Fioravanti Lui (2020)
Abstract Objective: Compared to standard spectacle lenses, do +0.40 EyeZenTM lenses reduce symptoms of asthenopia induced by computer? Methods: A prospective clinical study was carried out with 39 volunteers who spent more than 4 hours a day using a computer (age, 27.31±4.24; male: female =13:26). Asthenopia and visual comfort were assessed using a questionnaires. All participants completed the asthenopia questionnaire with updated regular lenses (baseline). After 4 weeks of +0.40 Eyezen™ lenses wearing all subjects answered the asthenopia questionnaire and a second questionnaire to establish their level of satisfaction with these lenses. Statistical analysis was performed usind the Shapiro-Wilk test and Wilcoxon test, and p-values less than 0.05 were considered statistically significant. Results: Compared to standard spectacle lenses (baseline), +0.40 EyeZenTM lenses wearing reduced the total asthenopia score from17.44 ± 5.51 to 13.18 ± 10.22 (p < 0.001). Regarding the perception of the visual comfort levels with these lenses in the management of digital devices, more than 90% of subjects said they were entirely or delighted with their visual comfort.. Conclusions: Digital asthenopia induced by computer was significantly reduced by +0.40 EyeZen lenses wearing.